Bone Marrow Mesenchymal Stem Cells Decrease the Expression of RANKL in Collagen-Induced Arthritis Rats via Reducing the Levels of IL-22 - Fang Li; Xin Li; Guiyan Liu; Chong Gao; Xiaofeng Li (Journal of Immunology Research)
Objective. To investigate the transplantation effect of bone marrow mesenchymal stem cells (MSCs) on the expression of interlukin-22 (IL-22) and RANKL in collagen-induced arthritis (CIA) rats. Methods. 32 CIA models were established. 16 CIA rats were transplanted with MSCs, and others were used as nontreatment CIA controls. The concentrations of IL-22 and RANKL in serum were detected by ELISA and those in synovial tissue of rats’ joints by immunohistochemical staining. In addition, the expression of RANKL mRNA was measured by RT-PCR in the fibroblast-like synoviocytes (FLSs), cultured with IL-22 in vitro, which were delivered from the joints of CIA rats treated with or without MSCs. Results. The transplantation of MSCs into CIA rats relieved the destruction of joints, measured by AI score, X-ray, and histopathology. MSCs also reduced the expression of IL-22 and RANKL in serum by ELISA (P<0.001) and similarly in FLSs by immunohistochemical staining. In vitro, IL-22 induced significantly the expression of RANKL mRNA in cultured FLSs in a dose-dependent manner, whereas this induction was significantly reduced in FLSs derived from CIA rats transplanted with MSCs (normal controls: F=79.33, P<0.001; CIA controls: F=712.72, P<0.001; and CIA-MSC rats: F=139.04, P<0.001). Conclusion. Our results suggest that the transplantation of MSCs can reduce the expression of RANKL in vivo by downregulating the levels of IL-22, thereby ameliorating the degree of RA bone destruction. This study provides a theoretical basis for a potential therapy of RA with MSCs, and IL-22 and RANKL may become two new targets to treat RA.